Challenges and lessons learnt from a sanitation project in rural Bolivia. Issue 7 (3rd October 2018) - Snyder, Katherine A.; Corral, Andrea F.; Woods, Gwendolyn J.; Prichard, Andrea; Montgomery, Melissa; Karanikola, Vasiliki
ABSTRACT: The University of Arizona chapter of Engineers Without Borders USA has faced multiple challenges involving community participation in rural development, in the Andean community of Marquirivi, Bolivia, both in rural design and in community participation. Despite successful construction of a shower house in 2014, the EWB-USA UA team experience with community participation revealed the numerous complexities involved in engaging successfully with communities. The importance of previous aid in a community with development projects also emerged as critical in shaping actions. This article discusses lessons learnt and recommendations for rural infrastructure projects, as well as the EWB-USA model of sustainable development.